Determination of non-cytotoxic antiviral concentrations of purine and indole derivatives in vitro - Iskra Sainova; Vera Kolyovska; Iliana Ilieva; Rumen Nikolov; Andrey Petrov; Radka Hadjiolova; Dimitrina Dimitrova-Dikanarova; Tzvetanka Markova (Pensoft Publishers, 2024)
Mammalian cells from lines derived from bovine embryonic trachea (EBTr) were used in the present study. After the formation of semi-confluent monolayers, one subpopulation of cells was inoculated with the vaccine avian poxvirus strain FK (fowl) and the other with the vaccine avian poxvirus strain Dessau (pigeon) (Poxviridae family). Twenty-four hours after viral inoculation, individual subsets of infected cells were treated with the purine derivative aminophylline and the remaining subsets with the indole derivative ergotamine tartrate, respectively. The effects of the analogues thus administered on the cells were recorded at the 24th hour and 48th hour after treatment with each substance, respectively. In cells inoculated with the FK viral strain and treated with both aminophylline and ergotamine tartrate, decreased cell viability was observed at all dilutions at the 48th hour post-treatment compared to the 24th hour. In aminophylline-treated cells, these differences were not statistically significant, unlike in ergotamine tartrate-treated cells, where they were statistically significant. In the same cells infected with the Dessau strain and treated with aminophylline, although decreased cell viability was found at the 48th hour of treatment compared to the 24th hour, in most cases no statistically significant differences were found. In cells infected with the same strain but treated with ergotamine tartrate, despite the lack of statistically significant differences, increased cell viability was seen at the 48th hour post-treatment compared to the 24th hour, specifically at the higher concentrations of 10-3 and 10-4 M/mL. These results suggest a lower cytotoxicity of aminophylline compared to ergotamine tartrate, but on the other hand, a higher anti-viral activity of ergotamine tartrate against the Dessau virus strain compared to aminophylline in in vitro conditions. Further studies need to be conducted in this regard.